Analysis of the Mapalus-Based Educational Management Model in Package C Equivalency Education in Minahasa Regency - Maringka, Riviva W; Rawis, Joulanda A M; Umbase, Ruth; Katuuk, Deitje A. (International Journal of Information Technology and Education, 2026)
Package C equivalency education represents a strategic non-formal education pathway aimed at expanding access to secondary education for individuals who are unable to participate in formal schooling. However, its implementation in Minahasa Regency faces several challenges, including low participation rates, inadequate facilities, limited tutor competence, and suboptimal program management. This study aims to analyze the planning, implementation, and evaluation processes of Package C education, identify supporting and inhibiting factors, and develop a contextual management model based on local cultural values, namely the Mapalus Model. This research employed a qualitative case study design. Data were collected through in-depth interviews, observations, and document analysis involving stakeholders such as education officials, PKBM/SKB managers, tutors, learners, and community leaders. Data analysis followed the interactive model of Miles and Huberman, including data reduction, data display, and conclusion drawing. The findings reveal that the management of Package C education has not been systematically implemented across all stages. Planning is not fully needs-based, implementation remains conventional, and evaluation is not optimally utilized. Supporting factors include stakeholder involvement and government support, while inhibiting factors include limited infrastructure, low community awareness, and a lack of tutor training. The study proposes a Mapalus-based management model emphasizing collaboration, participation, and collective responsibility. This model integrates participatory planning, collaborative organization, andragogical learning, continuous evaluation, and stakeholder synergy. The model is expected to improve the quality, relevance, and sustainability of equivalency education.